Klimat dla rozwoju przedsiębiorczości turystycznej w Małopolsce w świetle badań empirycznych - Dryglas, Diana; Wach, Krzysztof (Przedsiębiorczość - Edukacja, 2007)
The paper elaborates on the influence of regional factors (mezoenvironment) on tourist enter-prises development in the region. These factors create so called favorable regional climate fortourist entrepreneurship development. Analyzing impact of mezzoenvironment factors on to-urist enterprises development, the authors limit themselves only to small and medium-sizedtourist enterprises considering their dominant character in tourist sector, as well as the keysignificance for development of entrepreneurship and region or country competitiveness. Thearticle presents results of empirical research conducted on a random sample of small and me-dium-sized tourist enterprises in Ma³opolska Province.